Učinkovitost programov preprečevanja kajenja v šolah - Koprivnikar, Helena (Zdravstveno varstvo, 2010)
Almost all adult regular smokers start smoking in adolescence. It is thus important to focus on prevention of smoking among children and adolescents. School-based programmes for smoking prevention are one of the effective measures for achieving this. Numerous studies confirm moderate and short-term effectiveness of such programmes. Available data on long-term effectiveness ofthese programmes is limited, but there are studies that confirm that more intensive and complex programmes are effective all through the end of teenage years. Vast majority of primary schools in Slovenia implement different programmes and activities in the area of smoking prevention. Most often they perform the programme ''''Let''s promote nonsmoking''''. Programmes and activities are usually performed on voluntary basis, which does not assure long-term implementation of the programmes and evaluation of their effectiveness. We need to ensure unified and systematic development, implementation and evaluation of such programmes and activities in Slovenia.
Keywords: child; kajenje; mladostniki; nadzor; otroci; preprečevanje; šole